The 'chicken and egg' of subjective and social factors in desistance from crime - LeBel, T; Burnett, R; Maruna, S; Bushway, S (SAGE Publications, 2008)
It is now widely acknowledged that progression from persistent offending to desistance from crime is the outcome of a complex interaction between subjective/agency factors and social/environmental factors. A methodological challenge for desistance researchers is to unravel the differential impacts of these internal and external factors and the sequence in which they come into play. Towards this, the present investigation draws on a prospective study of 130 male property offenders, interviewed in the 1990s (the Oxford Recidivism Study), and followed up 10 years later. The analysis supports a 'subjective-social model' in which subjective states measured before release have a direct effect on recidivism as well as indirect effects through their impact on social circumstances experienced after release from prison.